2003
DOI: 10.1002/hfm.10049
|View full text |Cite
|
Sign up to set email alerts
|

Potential uses of technology to communicate risk in manufacturing

Abstract: Technological advances already implemented in other systems can be used to design and deliver warnings and other risk communications in a variety of occupational settings, including manufacturing environments. This article discusses technologies that could be used to design and deliver risk communications. Examples are discussed in terms of potential applications and protocols. As with many advancements, there are new challenges, including ethical considerations both inside and outside the workplace environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
4
0
4
Order By: Relevance
“…Some studies have examined the effect of dynamic features in signs on behavioral compliance during a work-related task and emergency [3,[58][59][60]. The findings suggested that dynamic presentations produced higher compliance than static presentations [58,[61][62][63][64][65] mainly because of some features that make them more noticeable. This is in line with attention theory [66].…”
Section: Related Workmentioning
confidence: 99%
“…Some studies have examined the effect of dynamic features in signs on behavioral compliance during a work-related task and emergency [3,[58][59][60]. The findings suggested that dynamic presentations produced higher compliance than static presentations [58,[61][62][63][64][65] mainly because of some features that make them more noticeable. This is in line with attention theory [66].…”
Section: Related Workmentioning
confidence: 99%
“…Current and new technology provides opportunities for more dynamic ways of warning people that would be potentially more effective. Several recent papers have explored this topic (Smith-Jackson & Wogalter, 2004;Wogalter & Conzola, 2002;Wogalter & Mayhorn, 2005). Here we focus on a few of the ways that technology may enhance warnings.…”
Section: Technology and Warningsmentioning
confidence: 99%
“…Advancements in technology enabled the design of dynamic warnings, incorporating displays, detectors, or sensor devices (Laughery & Wogalter, ). Several studies address the superior effectiveness of dynamic and technology‐supported warnings compared to static warning designs (Smith‐Jackson & Wogalter, ; Wogalter & Conzola, ; Wogalter & Mayhorn, ). According to Rogers et al (), to ensure the effectiveness of a warning, people have to notice, encode, comprehend, and comply to a warning.…”
Section: Warningsmentioning
confidence: 99%